Pengaruh Khitosan dan Media Campuran terhadap Pertumbuhan Semai Pisang Raja Bulu Raja bulu (Musa paradisiaca L var. sapientum) - Rosdiana Rosdiana; Helfi Gustia (Fakultas Pertanian - UMJ, 2018)
The productivity of banana, as priority fruit, is still low due to lack of good quality seedling. The research aim was to know the effect of chitosan application, mixed media and an interaction between mixed media with the chitosan on seedling growth of “raja bulu” banana. The research designed was a complete randomized block design with two factors. The first factor was the mixed soil, cow manure and rice husk charcoal and the second factor was chitosan at a concentration of 0, 2, 4, 6, and 8 ml L-1. Observed parameters were height, diameter, leaf number and biomass of seedling. The chitosan concentration at 4 ml L-1 gave the highest growth on the height (41.2 cm), leaf number (4.2 leaf plant-1) and dry weight (5.44 gr plant-1) raja bulu banana seedling. The mixed media of soil, cow manure with rice husk charcoal resulted in the highest growth of seedling height (46.6 cm), leaf number (5.2 leaf plant-1), dry weight (5.4 gr plant-1). Both chitosan applications and mixed media did not give significantly effect on the seedling diameter. The interaction between the mixture media with the application of chitosan did not significantly different on vegetative growth and seedling biomass.